1999
DOI: 10.1046/j.1365-313x.1999.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing by plants: the primary characteristics of signal perception and calcium response

Abstract: SummaryCold elicits an immediate rise in the cytosolic free calcium concentration ([Ca 2+ ] c ) of plant cells. We have studied the concerted action of the three underlying mechanisms, namely sensing, sensitisation and desensitisation, which become important when plants in the ®eld are subjected to changes in temperature. We applied different regimes of temperature changes with well-de®ned cooling rates to intact roots of Arabidopsis thaliana expressing the calcium-indicator, aequorin. Our results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
173
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 41 publications
12
173
0
1
Order By: Relevance
“…The single monophasic transient resembles the responses to osmotic stress, oxidative stress, and rapid cooling (Knight et al, 1996;Knight et al, 1997;Rentel and Knight, 2004), and prolonged responses have been reported in response to slow cooling (Plieth et al, 1999). Oscillations of calcium have been reported in guard cells responding to ABA and in legume root hairs responding to Nod factors (Wais et al, 2000;Allen et al, 2001), although it is important to note that the frequencies used here were not the same as those observed in guard and root hair cells.…”
Section: Cis-element Responses To Mastoparan Treatment Are [Ca 2+ ] Cmentioning
confidence: 76%
“…The single monophasic transient resembles the responses to osmotic stress, oxidative stress, and rapid cooling (Knight et al, 1996;Knight et al, 1997;Rentel and Knight, 2004), and prolonged responses have been reported in response to slow cooling (Plieth et al, 1999). Oscillations of calcium have been reported in guard cells responding to ABA and in legume root hairs responding to Nod factors (Wais et al, 2000;Allen et al, 2001), although it is important to note that the frequencies used here were not the same as those observed in guard and root hair cells.…”
Section: Cis-element Responses To Mastoparan Treatment Are [Ca 2+ ] Cmentioning
confidence: 76%
“…Transferring cells from 22°C to a lower temperature led to a progressive reduction in the suspension temperature; the lower the final temperature, the steeper the temperature decrease (not shown). Even though the final temperature was not sensed by the cells after 1 min, it appeared that the rate of temperature decrease was important for cold perception, as shown for the cold-elicited Ca 2+ influx [23].…”
Section: A Differential Labeling To Detect Ptdoh Proceeding Frommentioning
confidence: 95%
“…Under this unfavorable condition, several physiological changes are produced in plants manifested as senescence or wounds in photosynthetic tissues (SMIRNOFF, 1993). It was also observed that during periods of freezing temperatures, both stems and branches of some trees may also develop cracks (KOZLOWSKI et al, 1991;PLIETH, 1999;HARA et al, 2003).…”
Section: Results and Discusionmentioning
confidence: 99%